Identitas nasional sebagai pondasi: Tinjauan historis dan filosofis - Arrasyid, Muhammad Fariz (Maliki Interdisciplinary Journal, 2026)
National identity fundamentally serves as a cohesive force in sustaining unity within Indonesia’s pluralistic society. However, in contemporary political practice, its meaning has increasingly been contested and instrumentalized to advance particular group interests. This article aims to examine the tension between the ideal conception of national identity and the political reality characterized by adversarial and delegitimizing practices in Indonesia. This study employs a qualitative method using a literature review approach, drawing upon relevant scholarly journals and academic books. The findings reveal that democratization, while expanding political freedoms, has simultaneously intensified identity-based divisions, particularly along religious and nationalist lines, thereby contributing to heightened social polarization, declining public trust in governmental institutions, and the proliferation of misinformation. Moreover, the prevalence of unethical political communication practices, including excessive personal branding and performative political behavior, further undermines the substantive quality of democratic processes by privileging image over policy discourse. Therefore, this study underscores the necessity of reconstructing an inclusive and substantive understanding of national identity, alongside reinforcing political ethics, in order to ensure the resilience and sustainability of democracy in Indonesia.